1999
DOI: 10.1046/j.1365-2141.1999.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and functional effects of sphingolipids in blood cells

Abstract: Summary. We examined the sphingolipid metabolism of peripheral blood cells, i.e. platelets, erythrocytes, neutrophils and mononuclear cells. A distinguishing characteristic of sphingolipid metabolism in these highly differentiated cells was their high sphingosine (Sph) kinase activity. The occurrence of [ 3 H]sphingosine 1-phosphate (Sph-1-P) from [ 3 H]Sph (actively incorporated from the outside) in the blood cells was strong, long-lasting, and independent of cell activation. Hence, the possibility of Sph-1-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 47 publications
(91 reference statements)
2
101
0
1
Order By: Relevance
“…23 Consistent with our findings, it has been shown in other bulk cell studies of erythrocytes that the majority of intracellular sphingosine is in the phosphorylated form. 23,24,57 No other major fluorescent peaks except the internal standard were observed suggesting that under these conditions neither ceramide nor hexadecenal were formed in substantial quantities ( Figure 2 in the Supporting Information). This experiment demonstrated that SK activity could readily be detected in a cell lysate.…”
Section: Detection Of Enzymatic Activity In Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Consistent with our findings, it has been shown in other bulk cell studies of erythrocytes that the majority of intracellular sphingosine is in the phosphorylated form. 23,24,57 No other major fluorescent peaks except the internal standard were observed suggesting that under these conditions neither ceramide nor hexadecenal were formed in substantial quantities ( Figure 2 in the Supporting Information). This experiment demonstrated that SK activity could readily be detected in a cell lysate.…”
Section: Detection Of Enzymatic Activity In Cellsmentioning
confidence: 99%
“…It is known that erythrocytes avidly take up extracellular sphingosine, while storing and actively releasing S1P. 23,57 This release of S1P appears to be in response to an as yet unidentified plasma factor. 23 Consistent with our findings, it has been shown in other bulk cell studies of erythrocytes that the majority of intracellular sphingosine is in the phosphorylated form.…”
Section: Detection Of Enzymatic Activity In Cellsmentioning
confidence: 99%
“…Platelets contain stored S1P (27) and release it upon activation, thus contributing to serum S1P levels. Moreover, neutrophils, erythrocytes, endothelial cells, and mononuclear cells also release S1P (28,29). However, the mechanisms whereby S1P is released are poorly understood.…”
mentioning
confidence: 99%
“…Most, but not all, of the S1P release from platelets is dependent on stimuli such as thrombin and protein kinase C activation (Yatomi et al, 2000;Yatomi et al, 1997b), whereas erythrocytes release S1P constitutively (Ito et al, 2007;Yang et al, 1999). In contrast, it has been unclear where FTY720-P is produced.…”
Section: Introductionmentioning
confidence: 99%
“…Erythrocytes, platelets, and plasma were prepared as described elsewhere (Ito et al, 2007;Yang et al, 1999). Blood (~ 10 ml) was collected in 2 ml anticoagulant ACD (0.8% citric acid, 2.2% sodium citrate, and 2.45% glucose) then separated by centrifugation (120 x g for 15 min) into pellet and supernatant (platelet-rich plasma).…”
Section: Preparation Of Erythrocytes Platelets and Plasmamentioning
confidence: 99%